Association between maternal stress and premature milk cortisol, milk IgA, and infant health: a cohort study - Rosen-Carole, Casey B.; Greenman, Susan; Wang, Hongyue; Sonawane, Sharvari; Misra, Ravi; O'Connor, Tom; Järvinen, Kirsi; D'Angio, Carl; Young, Bridget E. (Frontiers in Nutrition, 2024)
Background: Maternal stress is pervasive in the Neonatal Intensive Care Unit (NICU). Maternal stress is associated with changes in human milk (HM) immunomodulatory agents, which may impact neonatal health. We sought to determine if maternal stress is associated with HM IgA and cortisol, and how HM components correlate with infant immune and neurodevelopmental outcomes. We then compared how these associations persist over time. Methods: This was a cohort study of exclusively breastfeeding mothers and their singleton moderately-preterm (28-34 weeks) infants in the NICU. We collected maternal serum, maternal saliva, whole milk and stress questionnaires at 1 and 5 weeks postpartum. We analyzed samples for HM IgA (customized immunoassay) and HM and salivary cortisol (chemiluminescent immunoassay). Infant illness was assessed using the Score for Neonatal Acute Physiology II (SNAP II) and SNAP II with Perinatal Extension (SNAPPE II), and infant neurodevelopment using the Test of Infant Motor Performance. We analyzed changes in HM IgA and cortisol over time using paired t tests. We performed correlation and regression analyses after adjusting for gestational age (GA), corrected GA, and infant days of life. Results: We enrolled 26 dyads (mean maternal age 28.1 years; 69% White; 19% Black; 8% Hispanic). Cortisol: Salivary and HM cortisol were closely associated in week 1 but not week 5. Though mean salivary cortisol remained stable over time (2.41 ng/mL (SD 2.43) to 2.32 (SD 1.77), p=0.17), mean HM cortisol increased (1.96ng/mL (SD 1.93) to 5.93ng/mL (SD 3.83), p<0.001). Stress measures were inversely associated with HM cortisol at week 1 but not week 5. IgA: HM IgA decreased over time (mean= -0.14mg/mL, SD 0.53, p<0.0001). High maternal stress on the PSS:NICU scale was positively associated with HM IgA at week 5 (r= 0.79, p=<0.001). Higher IgA was associated with a lower(better) SNAP II score at week 1 (r -0.74, p=0.05). No associations were found between maternal stress, salivary cortisol, HM cortisol, or HM IgA and neurodevelopment at discharge (TIMP). These relationships did not differ by infant sex. Conclusions: Maternal stress was associated with HM cortisol and HM IgA. HM IgA was associated with lower measures of infant illness.